A neutralizing anti–G‐CSFR antibody blocks G‐CSF–induced neutrophilia without inducing neutropenia in nonhuman primates. Issue 2 (17th May 2017) - Scalzo‐Inguanti, Karen; Monaghan, Katherine; Edwards, Kirsten; Herzog, Eva; Mirosa, Danijela; Hardy, Matthew; Sorto, Vicki; Huynh, Huy; Rakar, Steven; Kurtov, Daria; Braley, Hal; Wilson, Nick; et al.
Abstract : Antibody blockade of NHP G‐CSFR in vivo blocks STAT signaling without impacting peripheral neutrophil numbers or basic neutrophil functions. Abstract : Neutrophils are the most abundant WBCs and have an essential role in the clearance of pathogens. Tight regulation of neutrophil numbers and their recruitment to sites of inflammation is critical in maintaining a balanced immune response. In various inflammatory conditions, such as rheumatoid arthritis, vasculitis, cystic fibrosis, and inflammatory bowel disease, increased serum G‐CSF correlates with neutrophilia and enhanced neutrophil infiltration into inflamed tissues. We describe a fully human therapeutic anti–G‐CSFR antibody (CSL324) that is safe and well tolerated when administered via i.v. infusion to cynomolgus macaques. CSL324 was effective in controlling G‐CSF–mediated neutrophilia when administered either before or after G‐CSF. A single ascending‐dose study showed CSL324 did not alter steady‐state neutrophil numbers, even at doses sufficient to completely prevent G‐CSF–mediated neutrophilia. Weekly infusions of CSL324 (≤10 mg/kg) for 3 wk completely neutralized G‐CSF–mediated pSTAT3 phosphorylation without neutropenia. Moreover, repeat dosing up to 100 mg/kg for 12 wk did not result in neutropenia at any point, including the 12‐wk follow‐up after the last infusion. In addition, CSL324 had no observable effect on basic neutrophil functions, such as phagocytosis and oxidative burst. These data suggest that targeting G‐CSFR may provide a safe and effective means of controlling G‐CSF–mediated neutrophilia as observed in various inflammatory diseases.